Identity, accent aim, and motivation in second language users: New Scottish Gaelic speakers' use of phonetic variation. (8th June 2016) - Nance, Claire; McLeod, Wilson; O'Rourke, Bernadette; Dunmore, Stuart
Abstract : This paper examines the use of phonetic variation in word‐final rhotics among nineteen adult new speakers of Scottish Gaelic, i.e. speakers who did not acquire the language through intergenerational transmission. Our speakers learned Gaelic as adults and are now highly advanced users of the language. We consider variation in their rhotic productions compared to the productions of six older, traditional speakers. Previous approaches to variation in second language users have either focussed on how variable production will eventually result in native‐like 'target' forms (Type 1 study), or have investigated the extent to which second language users reproduce patterns of variation similar to 'native speakers' (Type 2 study). We additionally draw on sociocultural approaches to Second Language Acquisition and apply notions of accent aim, identity construction, and learning motivation in order to fully explore the data. In doing so, we advocate a 'Type 3' approach to variation in second language users. Abstract : Bheir am pàipear seo sùil air caochlaideachd fhògharach an cois fhuaimean le ruis (/r/) dheireannach am measg naoi deug luchd‐labhairt ùra na Gàidhlig, i.e. luchd‐labhairt nach do thog a' Ghàidhlig tro thar‐chur eadar‐ghinealach. Dh'ionnsaich an luchd‐labhairt seo a' Ghàidhlig nan inbhich, agus tha iad uile a' cleachdadh na Gàidhlig aig ìre àrd san latha an‐diugh. Sa phàipear seo bheir sinn sùil air caochlaideachd nan ruisean aig an luchd‐labhairt seo ann an coimeas ris a' chleachdadh a tha aig sia luchd‐labhairt dualchasach na Gàidhlig a tha nas sine. Gu ruige seo tha rannsachadh air caochlaideachd am measg luchd‐labhairt dàrna cànain air fòcas a chur air mar a dh'fhàsas caochlaideachd chànanach nas fhaisge air cleachdaidhean dualchasach na cànain 'targaid' (sgrùdadh Seòrsa 1), no air an ìre gus an cleachdar pàtranan dualchasach caochlaidh le luchd‐labhairt den t‐seòrsa ud (sgrùdadh Seòrsa 2). A thuilleadh air sin cleachdaidh sinn bun‐bheachdan sòisio‐chultarach ann an Togail Dàrna Cànain san sgrùdadh againn, a' cleachdadh amasan dualchainnt, cruthachadh fèin‐aithne agus adhbharan ionnsachaidh airson rannsachadh iomlan a dhèanamh air an dàta. Na lùib, molaidh sinn sgrùdadh 'Seòrsa 3' airson rannsachadh air caochlaideachd chànanach am measg luchd‐labhairt na dàrna cànain. [Scottish Gaelic]